Twenty-five years after the introduction of Evidence-based Medicine: knowledge, use, attitudes and barriers among physiotherapists in Italy — a cross-sectional study. Issue 6 (3rd June 2020) - Castellini, Greta; Corbetta, Davide; Cecchetto, Simone; Gianola, Silvia
Abstract : Objectives: To explore the knowledge, use, attitudes towards Evidence-based Medicine, also known as Evidence-based Practice (EBP), and perceived barriers to its dissemination among physiotherapists. Design: Cross-sectional study. Setting and participants: Members of the Italian Association of Physiotherapists (n=2000) were invited to participate in an online survey about EBP knowledge and use. Primary outcome measures: The survey questionnaire comprised four sections: (1) respondent characteristics; (2) knowledge of EBP principles; (3) attitude, use and perceived effectiveness of EBP; (4) perceived barriers to implementing EBP in clinical practice. Results: Out of 2000 physiotherapists, 1289 participated in the survey (64.5% response rate). Overall, 90% perceived EBP as useful and necessary for their clinical practice. More than 85% stated that they were familiar with the principles of EBP, 75% reported that they were able to search online databases for relevant information and 60% reported that they were able to understand statistical analyses. However, 56% believed that patient preferences and 39% that clinical expertise are not part of the EBP model. Half stated that they understood and could explain the term 'meta-analysis' but only 17% knew what a forest plot is and just 20% correctly judged the finding of a given meta-analysis. Lack of time was reported as the main barrier to EBP. Conclusion: The majority of Italian physiotherapists overrated their knowledge about EBP, demonstrating a gap between perceived and actual knowledge of EBP in this population.